HOME CARE ACTIVITIES IN THE CASE OF FRACTURES POST OPERATION H+17 TRAFFIC ACCIDENTS - Rizaludin Akbar; Anita Faridhawati; Dede Roheti; Kirani Wulandari (Jurnal Abdisci, 2024)
We have prepared the report on the results of the nursing study program's home visit activities correctly, Faculty of Health Sciences, University of Muhammadiyah Cirebon. Traffic accidents (KLL) are one of Indonesia's most significant causes of death. The large number of victims will have a significant economic and social impact (material losses) and various preventive efforts to improve traffic by involving various related parties, but the results are not as expected. Home Care services are expected to be able to apply a healthy lifestyle and pay attention to their welfare, primarily related to health